Provider Preference, Logistical Challenges, or Vaccine Hesitancy? Analyzing Parental Decision-Making in School Vaccination Programs: A Qualitative Study in Sydney, Australia - Leigh McIndoe; Alexandra Young; Cristyn Davies; Cassandra Vujovich-Dunn; Stephanie Kean; Michelle Dives; Vicky Sheppeard (Vaccines)
Background: School-based immunization programs are crucial for equitable vaccine coverage, yet their success depends on parental consent processes. This study investigates patterns of vaccine decision-making within Australia’s school-based immunization program, specifically focusing on human papillomavirus (HPV) and diphtheria-tetanus-pertussis (dTpa) vaccines offered free to adolescents aged 12–13. Methods: This qualitative study was conducted in the South Eastern Sydney Local Health District (2022–2023). Semi-structured interviews were held with school staff (n = 11) across government, Catholic, and independent schools, parents whose children were not vaccinated at school (n = 11) and a focus group with public health unit staff (n = 5). Data were analyzed to identify key barriers and patterns in vaccine decision-making. Results: Analysis revealed three distinct groups of parents whose children were not vaccinated through the school program: (1) those favoring general practitioners for vaccination, driven by trust in medical providers and a preference for personalized care; (2) those intending to consent but facing logistical barriers, including communication breakdowns and online consent challenges; and (3) vaccine-hesitant parents, particularly regarding HPV vaccination, influenced by safety concerns and misinformation. These findings demonstrate that non-participation in school vaccination programs should not be automatically equated with vaccine hesitancy. Conclusions: Tailored interventions are necessary for addressing vaccine non-participation. Recommendations include strengthening collaboration with general practitioners, streamlining consent processes and providing targeted education to counter misinformation. This study provides valuable insights into social determinants of vaccine acceptance and offers actionable strategies for improving vaccine uptake in school-based programs.